2019
DOI: 10.1109/tap.2019.2930126
|View full text |Cite
|
Sign up to set email alerts
|

Memory Footprint Reduction for the FFT-Based Volume Integral Equation Method via Tensor Decompositions

Abstract: We present a method of memory footprint reduction for FFT-based, electromagnetic (EM) volume integral equation (VIE) formulations. The arising Green's function tensors have low multilinear rank, which allows Tucker decomposition to be employed for their compression, thereby greatly reducing the required memory storage for numerical simulations. Consequently, the compressed components are able to fit inside a graphical processing unit (GPU) on which highly parallelized computations can vastly accelerate the ite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Frequency: The work presented in [42] showed that the rank of the integral operators for 3D problems increases linearly with respect to the operating frequency. This was confirmed in [10], for the BTTB defining tensors of the FFT-based VIE systems (discretized integral operators). These tensors were columns of the corresponding Galerkin MoM matrices and modeled the interactions between one voxel's basis function and the whole domain via the N or K operators.…”
Section: A Tucker Rank Behaviormentioning
confidence: 59%
See 2 more Smart Citations
“…Frequency: The work presented in [42] showed that the rank of the integral operators for 3D problems increases linearly with respect to the operating frequency. This was confirmed in [10], for the BTTB defining tensors of the FFT-based VIE systems (discretized integral operators). These tensors were columns of the corresponding Galerkin MoM matrices and modeled the interactions between one voxel's basis function and the whole domain via the N or K operators.…”
Section: A Tucker Rank Behaviormentioning
confidence: 59%
“…The aim of this work is to use Tucker decomposition [17] to perform a column-wise compression of the VSIE coupling matrix, in order to limit the associated memory demand and enable the computation of the relevant matrix-vector products in GPUs. Our approach was motivated by previous work [10] on the reduction of the memory footprint of FFT-based VIE Green's function tensors and the acceleration of matrix-vector products in VIE using GPU. Tucker decomposition belongs to a larger family of tensor decompositions and have been used successfully in the past for matrix compression inside IEbased simulations for EM applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conductive, dielectric, and magnetic media can be considered by the proposed FFT-PEEC method and both linear and non-linear media can be considered. As proposed in [49], further computational improvements can be obtained with the adoption of a Graphical Processing Unit (GPU) that can speed-up the voxelization process and, mostly, the matrix-vector products via FFT. Moreover, when the considered devices have parts with very different dimensions (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Since it was shown that the performance of GMT is not affected by the size of the voxel [20], it will be desirable to use clinical resolutions (∼ 1 mm) for future in-vivo translation. One possible solution that will be explored to make that feasible is to compress the VIE operators using the Tucker decomposition [47], [48], which should allow us to perform the necessary matrix-vector products in GPUs even at high spatial resolutions [49]. Moreover, GMT could be further accelerated to facilitate in-vivo applications by applying a recently proposed preconditioner for the solution of the forward problem [25].…”
Section: Discussionmentioning
confidence: 99%